A Rare Encounter of a Lithopedion: A Case Report (Nepalese Journal of Radiology, 2025)
Lithopedion (lithos = rock and paidion = child) is a rare condition that usually occurs in extra uterine pregnancies. The incidence of lithopedion is approximately 0.00045% of all pregnancies. In this condition, the ectopic fetus dies and is not absorbed by the mother’s body. The dead fetus is coated by a calcified shell around it which protects it from maternal immunity. We report a case of a 65-year-old woman who had lithopedian for 20 years and was discovered incidentally at our center.